Safety considerations in the treatment with anti-CGRP(R) monoclonal antibodies in patients with migraine - Van Der Arend, Britt W. H.; Van Veelen, Nancy; De Ruijter, Joëlle E. T.; Olsen, Michael H.; MaassenVanDenBrink, Antoinette; Terwindt, Gisela M. (Frontiers in Neurology, 2024)
Background Anti-CGRP-(receptor-)monoclonal antibodies (anti-CGRP(R)-mAbs) represent a novel class of drugs for migraine treatment, but their long-term cerebrovascular and cardiovascular (CV) safety warrants further examination. Methods In this observational cohort study we assessed the CV safety for erenumab and fremanezumab in a real-world setting during a follow-up period of at least 1 year. Patients with hypertension or CV history were excluded. We conducted ECGs and collected clinical data at treatment initiation and thereafter every 3 months, including liver and kidney function, lipid-, electrolyte-and glucose levels. Results Among patients receiving erenumab (n = 101) or fremanezumab (n = 92), 3.1% (6/193) developed abnormal ECGs or CV adverse events. Of these, three (1.6%) experienced moderate to severe CV adverse events (cerebellar stroke, spontaneous coronary artery dissection, and pericarditis) and discontinued treatment. The remaining three (1.6%) developed non-threatening ECG abnormalities without physical complaints. No significant changes were observed in liver and kidney function, lipid-, electrolyte-, or glucose levels. Discussion We observed CV events in 1.6% of patients with 1.5-year follow-up of anti-CGRP(R)-mAbs treatment. We advise awareness regarding CV events in patients with migraine undergoing CGRP-targeted treatment, not as a confirmation of increased risk but as a proactive measure to address potential multifactorial influences.